Aldehyde Dehydrogenase 2 Ameliorates LPS-Induced Acute Kidney Injury through Detoxification of 4-HNE and Suppression of the MAPK Pathway. (6th April 2023) - Jin, Jifu; Chang, Rebecca Suchi; Xu, Sujuan; Xia, Guang; Wong, Jennifer Ming Jen; Fang, Yi; Jia, Ping; Ding, Xiaoqiang
Abstract : Lipopolysaccharide (LPS)-induced septic acute kidney injury (AKI) is determined as a devastating organ dysfunction elicited by an inappropriate response to infection with high morbidity and mortality rates. Previous evidence has illustrated an indispensable role of mitochondrial aldehyde dehydrogenase 2 (ALDH2) in the pathogenesis of sepsis-induced multiorgan abnormalities. Specifically, this study investigated the potential role of ALDH2 in sepsis-induced AKI. After LPS administration, we observed a significant decline in renal function, increased inflammatory cytokines, oxidative stress, 4-hydroxy-2-nonenal (4-HNE) accumulation, and apoptosis via MAPK activation in ALDH2 −/− mice; in contrast, pretreatment with Alda-1 (an ALDH2 activator) alleviated the LPS-induced dysfunctions in mice. Moreover, in vitro analysis revealed that ALDH2 overexpression in mouse tubular epithelial cells (mTECs) improved the inflammatory response, oxidative stress, 4-HNE accumulation, and apoptosis via MAPK inhibition, whereas ALDH2 knockdown in mTECs aggravated these parameters via MAPK activation. Therefore, ALDH2 may protect against LPS-induced septic AKI by suppressing 4-HNE/MAPK pathway.